Age-related exacerbation of lung damage after trauma is associated with increased expression of inflammasome components - Zhou, Yuzhuo; Meng, Fanshuai; Köhler, Kernt; Bülow, Jasmin Maria; Wagner, Alessa; Neunaber, Claudia; Bundkirchen, Katrin; Relja, Borna (Frontiers in Immunology, 2024)
Background: Trauma, a significant global cause of mortality and disability, often leads to fractures and hemorrhagic shock, initiating an exaggerated inflammatory response, which harms distant organs, particularly the lungs. Elderly individuals are more vulnerable to immune dysregulation posttrauma, leading to heightened organ damage, infections, and poor health outcomes. This study investigates the role of NF-κB and inflammasomes in lung damage among aged mice post-trauma.Methods: Twelve male C57BL/6J mice underwent hemorrhagic shock and a femoral fracture (osteotomy) with external fixation (Fx) (trauma/hemorrhage, THFx), while another 12 underwent sham procedures. Mice were categorized into young (17-26 weeks) and aged (64-72 weeks) groups (n=6). After 24h, lung injury was assessed by hematoxylin-eosin staining, prosurfactant protein C (SPC) levels, HMGB1, and Muc5ac qRT-PCR. Gene expression of Nlrp3 and Il-1b, and protein levels of IL-6 and IL-1b in lung tissue and bronchoalveolar lavage fluid were determined. Levels of lung-infiltrating polymorphonuclear leukocytes (PMNL) and activated caspase-3 expression to assess apoptosis, as well as NLRP3, ASC, and Gasdermin D (GSDMD) to assess the expression of inflammasome components were analyzed via immunostaining. To investigate the role of NF-κB signaling, protein expression of phosphorylated and non-phosphorylated p50 were determined by western blot.Results: Muc5ac, and SPC as lung protective proteins, significantly declined in THFx versus sham. THFx-aged exhibited significantly lower SPC and higher HMGB1 levels versus THFx-young. THFx significantly increased activated caspase-3 versus both sham groups, and THFx-aged had significantly more caspase-3 positive cells versus THFx-young. IL-6 significantly increased in both sham and THFx-aged groups versus corresponding young groups. THFx significantly enhanced PMNL in both groups versus corresponding sham groups. This increase was further heightened in THFx-aged versus THFx-young. Expression of p50 and phosphorylated p50 increased in all aged groups, and THFx-induced p50 phosphorylation significantly increased in THFx-aged versus THFxyoung. THFx increased the expression of inflammasome markers IL-1β, NLRP3, ASC and GSDMD versus sham, and aging further amplified these changes significantly.This study's findings suggest that the aging process exacerbates the excessive inflammatory response and damage to the lung following trauma. The underlying mechanisms are associated with enhanced activation of NF-κB and increased expression of inflammasome components.